Mechanical properties of bovine hydroxyapatite (BHA) composites doped with SiO2, MgO, Al2O3, and ZrO2 - GÜNDÜZ, OĞUZHAN; SALMAN, SERDAR; BOZKURT, YAHYA (SPRINGER, 2007)
Biologically derived hydroxyapatite from calcinated (at 850 degrees C) bovine bones (BHA) was doped with 5 wt% and 10 wt% of SiO2, MgO, Al2O3 and ZrO2 (stabilized with 8% Y2O3). The aim was to improve the sintering ability and the mechanical properties (compression strength and hardness) of the resultant BHA- composites. Cylindrical samples were sintered at several temperatures between 1,000 and 1,300 degrees C for 4 h in air. The experimental results showed that sintering generally occurs at 1,200 degrees C. The BHA-MgO composites showed the best sintering performance. In the BHA-SiO2 composites, extended formation of glassy phase occurred at 1,300 degrees C resulting in structural degradation of the resultant samples. No sound reinforcement was achieved in the case of doping with Al2O3 and zirconia probably due to the big gap between the optimum sintering temperatures of BHA and these two oxides.
Keywords: SINTERING TEMPERATURE; ZIRCONIA; BONE; BIOCERAMICS; STABILITY; ADDITIVES; CERAMICS; GLASSES; SYSTEM; CAF2